3D Pop Up Big Book for Elementary English Animal Literacy - Chandrika Rahmania Cahyani; Fika Megawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Visual learning media are widely utilized to support literacy development among elementary school students through engaging instructional materials. Specific Background: Big Book media, characterized by large text and illustrations, has been adapted into a Pop Up 3D format to create interactive reading materials introducing animal species and habitats in English. Knowledge Gap: Existing Big Book learning media are commonly available in standard formats and rarely integrate oversized layouts with three-dimensional page displays across the entire content. Aims: This study aims to develop and describe the design and content of a handmade 3D Pop Up Big Book that supports reading activities and student engagement in elementary English learning. Results: The developed product consists of five themed pages presenting animals including lion, elephant, butterfly, frog, and dolphin, each accompanied by descriptive English text and visually raised pop-up illustrations. The book uses contrasting colors, sticker-based imagery, cardboard structure, and large-format text to facilitate literacy activities and interactive teacher-student learning procedures, including predictive reading and 5W+1H questioning strategies. Novelty: The integration of oversized Big Book format with full-page 3D pop-up elements and handmade instructional design represents a distinctive learning media model combining visual storytelling and literacy practice. Implications: The product provides an alternative instructional resource that supports reading practice, student participation, and teacher creativity in developing engaging English literacy learning for elementary education. Highlights: The Learning Product Integrates Raised Visual Illustrations With Large-Scale Printed Storytelling Materials. The Material Introduces Five Animal Habitat Themes Supported by Descriptive English Narration. Instructional Procedures Incorporate Predictive Questioning Strategies During Classroom Literacy Activities. Keywords: 3D Big Book, Pop Up Learning Media, Elementary English Literacy, Animal Habitat Learning, Visual Reading Media